Carcass yield, non-carcass parts, internal organs and meat quality characteristics of karayaka male lambs with different birth weight fed free-choice feeding - Yildirim, Arda; Ulutaş, Zafer; Ocak, Nuh; Kaptan, Muhammet (Penerbit Universiti Kebangsaan Malaysia, 2017)
In order to investigate the changes in meat quality characteristics and some serum metabolites as well as carcass yield, non-carcass parts, internal organs of lambs as influenced by birth weight (BtW) and feeding system (FS), 28 Karayaka male lambs (150 days of age) obtained from four comparable groups that consisted of seven replicates according to a 2 × 2 factorial arrangement for 2 BtW (low, 4.1 ± 0.06 kg and high, 5.0 ± 0.09 kg) and 2 FS (total mixed ration, TMR and free choice feeding, FCF) were used. After weaning (90 days of age), lambs with low BtW and high BtW were fed individually a TMR ad libitum or fed on the same ingredients (FCF) as that of TMR. The TMR was consisted of 80% of a compound feed and 20% of roughage based on a dry matter basis (140 g crude protein and 10.7 ME MJ/kg). The carcass weight and yield of lambs were not affected by the BtW, FS and BtWxFS interaction. The slaughter body weight, cold carcass weight and yield of FCF-fed lambs were higher than those of TMR-fed animals. The pH45 and shear force of semitendinosus muscle decreased and increased by the FCF systems, respectively. These results showed that BtW of lambs did not affect the studied parameter and that feeding system created more differences in terms of some parameters due to the fact that the FCF lead to improvement in carcass and some meat quality traits.